2016
DOI: 10.1002/bimj.201500233
|View full text |Cite
|
Sign up to set email alerts
|

Blinded versus unblinded estimation of a correlation coefficient to inform interim design adaptations

Abstract: Regulatory authorities require that the sample size of a confirmatory trial is calculated prior to the start of the trial. However, the sample size quite often depends on parameters that might not be known in advance of the study. Misspecification of these parameters can lead to under‐ or overestimation of the sample size. Both situations are unfavourable as the first one decreases the power and the latter one leads to a waste of resources. Hence, designs have been suggested that allow a re‐assessment of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…(c) What was the difference in these effects across the three paradigms? We evaluated (a) in terms of absolute units (mV) using blinded covariate analysis [ 43 ], and (b), (c) in terms of both absolute units and relative units (% change). For absolute units, we computed the peak-peak amplitudes of the MEPs and averaged them across the 15 trials.…”
Section: Methodsmentioning
confidence: 99%
“…(c) What was the difference in these effects across the three paradigms? We evaluated (a) in terms of absolute units (mV) using blinded covariate analysis [ 43 ], and (b), (c) in terms of both absolute units and relative units (% change). For absolute units, we computed the peak-peak amplitudes of the MEPs and averaged them across the 15 trials.…”
Section: Methodsmentioning
confidence: 99%
“…Further, a blinded estimation of the correlation coefficient based on interim data at the midcourse of a trial can be a suitable solution to avoid an underpowered or overpowered trial. 33 Nonetheless, this method has been developed for a trial to compare continuous endpoints. Therefore, further extensions of methods proposed for two co-primary endpoints, including overdispersed count and continuous outcomes, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, rough correlation values must be estimated by using other metrics (such as coefficient of determination) from a systematic review of medical literature, as shown in Section 4. Further, a blinded estimation of the correlation coefficient based on interim data at the midcourse of a trial can be a suitable solution to avoid an underpowered or overpowered trial 33 . Nonetheless, this method has been developed for a trial to compare continuous endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Existing work in this context has mainly focused on trials with multiple endpoints. [14] approached the sample size calculation of trials with multiple, correlated endpoints. They proposed estimators for the covariance and the correlation based on blinded data obtained at an interim analysis.…”
Section: Introductionmentioning
confidence: 99%